Estimation of Some Genetic Parameters of Four Genotypes of Bread Wheat under of Spraying Application of Nano-Potassium - Meften, Mohanad Turki; AL-Jana, Mohammed Hussein Noor; Fadel, Hassan Abbas (American Journal of Biodiversity, 2025)
A field experiment were conducted at the second agricultural research and experiment station of the College of Agriculture at the University of Al-Muthanna, which is located in the village of Al Bandar, southwest of Al-Muthanna Governorate. During the winter agricultural season 2022-2023, To find out the effect of spraying three different levels of Nano-potassium fertilizer (0, 1.5, 3 g. L-1) which is symbolized by (K0, K1, K2) on growth characteristics and the yield of four genotypes of wheat (N2, N8 and N12) as well as variety (Aba-99) according to the Randomized Complete Block Design (R.C.B.D) with three replications. the results showed that there were significant differences between the treatments of the genotypes in most of the growth and yield characteristics. The genotype N12 gave the highest average plant height, reaching 84.78 cm, the number of tillers was 8.92 tiller per plant, the weight of a thousand grain was 40.79 (g), the number of grains per spike was 45.27 grains, and the harvest index was 30.82%, while the variety Aba 99 excelled in flag leaf area of the, reaching 34.38 cm2. As well as there were significant differences between the levels of potassium in most of the growth characteristics obtained, where the K2 level gave the highest average plant height, reaching 87.18 cm, the flag leaf area was 34.38 cm2, the number of tillers per plant was 9.00 tiller, length of spike which was 11.30 cm, the weight of a thousand grain was 41.08 (g), and the number of grains per spike 49.94, the yield is 4.73 tons per hectare, and the biological yield is 18.64 tons per hectare. While the results indicated significant differences for interaction between genotype and potassium levels in most of the growth characteristics obtained, as the (K2 × N12) treatment excelled in plant height of 92.08 cm, number of tillers per plant 10.78, weight of a thousand grains 48.38 (g), number of grains per spike 54.47 grains, and grain yield of 5.75 tons. Per hectare and harvest index 30.30%. As for broad sense heritability, the traits gave highest percent they are the flag leaf area, the number of tiller per plants, the number of grains per spike, the plant height and the harvest index, whose heritability reached (99.15, 97.30, 96.40, 92.24 and 77.57) respectively, Which can be adopted as a selection function to improve the genetic compositions under study.